Pengaturan Lalulintas Kereta Api di Stasiun Cicalengka untuk Mendukung Pengoperasian Jalur Ganda Kereta Api Bandung-Cibatu - Dian Setiawan M; Rahardhita Luthfiana Devi P; Sri Atmaja P Rosyidi (Semesta Teknika, 2018)
Indonesian Railway Authority plans to build a double railway track between Bandung-Cibatu which is currently the densest service line in Bandung Regency. Cicalengka Station is one of the major stations in this line service. This study aims to plan the train traffic arrangement at Cicalengka Station. The Conflict Rate Matrix Table was used as a simple simulation method to analyse the train journey route (formed, used, conflicted) and the degree of route usage against train frequency. The results showed that the Cicalengka Station on double track system would be passed by 98 passenger trains and planned to have two primary track (II and III) which are used for the direct train journey through the station. Track I, IV, V, and VI are the siding tracks that used for a railway stop. Cicalengka Station is also planned to have a route that is formed and is used each amounted to 10 routes (A to J). The conflict degree is 0.84, and the degree of route usage against train frequency is 0.75. Furthermore, it can be concluded that the percentage of non-conflicted route increased from 16% to 25%.